Analysis Of Quality Websites, Social Media, And Influencer Marketing Based On Halal Food Products On Purchase Decisions At Mie Gacoan Mansyur Branch, Medan - Santika, Eva; Surya, Elfitra Desy; Sanny, Annisa (Jurnal Fokus Manajemen, 2025)
This study aims to test and analyze the influence of website quality, social media, and influencer marketing based on halal food products on consumer purchase decisions at Mie Gacoan Mansyur Branch in Medan City. The research method used is a quantitative approach based on positivism with purposive sampling techniques. The data was collected through a questionnaire distributed to consumers who had made a purchase for three months. The sample totaled 96 respondents, and the data was analyzed using the SmartPLS application. The results of the study show that the quality of websites, social media, and influencer marketing have a positive and significant influence on purchasing decisions, respectively. This study has limitations in the scope of location and the number of respondents that only cover one restaurant branch. These findings contribute to the field of digital marketing and the halal food industry, and can be a reference for culinary business actors in optimizing digital marketing strategies that are in accordance with halal values to encourage consumer purchase decisions..